2019
DOI: 10.3171/2017.11.jns171510
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cerebrospinal fluid on blood coagulation and the implications for ventriculovenous shunting

Abstract: OBJECTIVEThe effect of CSF on blood coagulation is not known. Enhanced coagulation by CSF may be an issue in thrombotic complications of ventriculoatrial and ventriculosinus shunts. This study aimed to assess the effect of CSF on coagulation and its potential effect on thrombotic events affecting ventriculovenous shunts.METHODSTwo complementary experiments were performed. In a static experiment, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…When CSF is infused, ACT remains stable whereas both CR and PF increase significantly more than in RL and CTRL groups. This finding confirms the coagulation enhancing effect of CSF, 23 which seems to compensate for the fibrinogen deprivation and the consumption of clotting factors due to the in vitro test.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…When CSF is infused, ACT remains stable whereas both CR and PF increase significantly more than in RL and CTRL groups. This finding confirms the coagulation enhancing effect of CSF, 23 which seems to compensate for the fibrinogen deprivation and the consumption of clotting factors due to the in vitro test.…”
Section: Discussionsupporting
confidence: 81%
“…The infusion of fluids results in hemodilution that may bias the results. The rate of 2 ml/h in combination with limited duration of 60 min for each circuit was chosen to minimize hemodilution and related blood coagulation disturbances: 23 By limiting the duration of the experiment and the infusion rate, the volume percentage of the infusion fluid was only 5.88% at the end of the experiment. This is significantly lower than 9%–11%, which is the known threshold for infusion fluids like CSF and RL to affect blood coagulation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Since the venous pressure in the superior sagittal sinus was 5-10 cmH 2 O, and the lowest pressure in the Medtronic adjustable shunt tube was 5 cmH 2 O, the high cranial pressure hydrocephalus shunt had a better effect. It has been reported that low cranial pressure or normal pressure ventriculosinus shunt has a poor prognosis (10,11). In this group, 2 cases were cured after ventriculo-bladder shunt due to low preoperative intracranial pressure and no significant changes in postoperative symptoms and ventricular size.…”
Section: Discussionmentioning
confidence: 74%
“…Some in vitro studies showed that adding CSF to blood makes blood hypercoagulable. They found the accelerated conversion from fibrinogen to fibrin, gradual shortening of the activated clotting time, increased the clot rate, and higher platelet activation after the addition of CSF [25,26]. Indeed, CSF contains tissue factor and coagulation proteins.…”
Section: Csfmentioning
confidence: 99%
“…Apart from these clotting factors, immunoglobulins and other immunological factors in CSF can cause neuroinflammation, leading to a procoagulant state [17]. In pathological conditions, the concentration of coagulation proteins and the imbalance between tissue factor and tissue factor pathway inhibitor even increase, resulting in a more pronounced procoagulant effect of CSF [26,27]. However, adding CSF to blood enhances coagulability requiring a starting concentration of 5-9%.…”
Section: Csfmentioning
confidence: 99%